Comparison of trans-umbilical single-port laparoscopic surgery and laparotomy for repair of perforated peptic ulcer in pediatric patients: a retrospective study - Jyun-Hong Jiang; Shin-Yi Lee; Hsuan-Fan Tung; Yi-Wen Tsai (BMC Surgery)
Abstract Background Perforated peptic ulcer (PPU) is an uncommon condition in children. The evolution of the surgical procedures may influence the outcomes of the patients and analysis of our results support the notion. Materials and methods The medical records of children aged 0 to 18 years who underwent surgery for PPU from 2000 to 2017 in Kaohsiung Chang Gung Memorial Hospital were retrospectively reviewed. Patient demographics, perioperative and intraoperative details, and surgical outcomes were analyzed. Results Fourteen patients were identified. The mean age of the study group was 15 years (range: 2.8 to 16 years). Eight patients underwent trans-umbilical single-port laparoscopic (TUSPL) repair and four had laparotomy repair. There was no significant difference in patient demographics between the groups. The mean perforation size and operating time were similar in both groups. The median length of hospital stay was shorter in the TUSPL group than in laparotomy group(4.5 days and 7 days respectively, p = 0.154). The median pain score on postoperative day one was lower in the TUSPL group than in the laparotomy group (3 and 4.5 respectively, p = 0.109). The total number of doses of intravenous analgesics after operation was reduced in the TUSPL group compared with the laparotomy group( median 0.5 and 5.5 respectively, p = 0.004). Conclusion Compared with laparotomy, the TUSPL approach for peptic ulcer repair can reduce post-operative pain and shorten the hospital stay. TUSPL repair is a feasible treatment for PPU in pediatric patients without shock.